2011
DOI: 10.1002/chir.21013
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and mechanical anharmonicities from NIR‐VCD spectra of compounds exhibiting axial and planar chirality: The cases of (S)‐2,3‐pentadiene and methyl‐d3 (R)‐ and (S)‐[2.2]paracyclophane‐4‐carboxylate

Abstract: The IR and Near infrared (NIR) vibrational circular dichroism (VCD) spectra of molecules endowed with noncentral chirality have been investigated. Data for fundamental, first, and second overtone regions of (S)-2,3-pentadiene, exhibiting axial chirality, and methyl-d 3 (R)-and (S)-[2.2]paracyclophane-4-carboxylate, exhibiting planar chirality have been measured and analyzed. The analysis of NIR and IR VCD spectra was based on the local-mode model and the use of density functional theory (DFT), providing mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
(65 reference statements)
0
10
0
Order By: Relevance
“…A compariwww.eurjoc.org son of the experimental VCD spectra of the two diastereomers (R p ,R)-4 and (R p ,S)-4 (X = iPr) with the corresponding calculated VCD spectra is shown in Figure 4, and the experimental VCD spectra of the two diastereomers (S p ,R)-5 and (S p ,S)-5 (X = tBu) are compared with the corresponding calculated VCD spectra in Figure 5. In Figure 6 and 7 the experimental VCD spectra of the two dia- Our previous studies on paracyclophanes [30,32,33] showed that vibrational features associated with the quinolinophane moiety should be expected above 1500 cm -1 , whereas the region below 1500 cm -1 is more affected by the aliphatic why quinolinophane is so unusual. Related to each band there are several vibrational transitions, in particular, the band at approximately 1590 cm -1 contains three modes, whereas the bands at approximately 1560 and 1500 cm -1 contain two modes each.…”
Section: Vcd Spectramentioning
confidence: 89%
See 4 more Smart Citations
“…A compariwww.eurjoc.org son of the experimental VCD spectra of the two diastereomers (R p ,R)-4 and (R p ,S)-4 (X = iPr) with the corresponding calculated VCD spectra is shown in Figure 4, and the experimental VCD spectra of the two diastereomers (S p ,R)-5 and (S p ,S)-5 (X = tBu) are compared with the corresponding calculated VCD spectra in Figure 5. In Figure 6 and 7 the experimental VCD spectra of the two dia- Our previous studies on paracyclophanes [30,32,33] showed that vibrational features associated with the quinolinophane moiety should be expected above 1500 cm -1 , whereas the region below 1500 cm -1 is more affected by the aliphatic why quinolinophane is so unusual. Related to each band there are several vibrational transitions, in particular, the band at approximately 1590 cm -1 contains three modes, whereas the bands at approximately 1560 and 1500 cm -1 contain two modes each.…”
Section: Vcd Spectramentioning
confidence: 89%
“…Our previous studies on paracyclophanes [30,32,33] showed that vibrational features associated with the quinolinophane moiety should be expected above 1500 cm -1 , whereas the region below 1500 cm -1 is more affected by the aliphatic substituents. We found that the quinolinophane moiety provides an unambiguous signature of the planar chirality, and this was common to all thirteen compounds 1-8; the spectrum consists of a triplet of VCD bands at approximately 1590, 1560, and 1500 cm -1 with (+,+,-) signs for (R p ) and (-,-,+) signs for (S p ).…”
Section: Vcd Spectramentioning
confidence: 97%
See 3 more Smart Citations